Effective design of stiffeners on industrial ducts - Udall, Jeff (My University, 2007)
Large ducts are used to carry air and flue gases to and from industrial processes and can be subjected to a variety of loading conditions. To maintain the structural integrity of the ducts, stiffeners are attached to the casing to form a more rigid frame. Stiffeners protect the duct casing by reducing the unsupported span of the plate, hold the original shape of the duct, and are used for overall duct support or restraint.
Current methods used to size stiffeners on industrial ducts are derived from standard equations used for beam design in buildings with some accommodation for the composite section formed by the beam and casing plate. These methods are shown to be significantly conservative with a safety factor in the order of four to five. This large conservatism in the design results in higher capital costs and construction costs.
To determine the actual capacity of a stiffener beam relative to the design limit, an experimental program was developed. A box was fabricated with a removable top plate that incorporated one of two different beam stiffeners. The box was subjected to a vacuum pressure and the response of the beams was monitored until their final collapse.
A finite element model was developed to simulate the experiment. Reasonable agreement between the finite element model and the experimental data was found. Subsequently, a parametric study was conducted using the developed finite element model.
An alternative analytical design method was presented that took into account composite action. This includes the location of the neutral axis, the location of the load along the height of the beam, and the contribution of the web to the support of the outstanding compression flange. Each of these factors provides an increase in bending capacity for the stiffener.
The proposed alternative method continues to provide conservative results relative to the point of failure determined by both the experimental program and the finite element analysis. However, the results are substantially less conservative than what is provided through the current design methods.
Keywords: design; stiffeners; industrial; ducts